Nursing Care for Pneumonia Patients - Lail, Nur Alfi; Efendi, Ramli; Tri Noviyan, Arina; Lestari, Inka; Ahmad Fausi, Adhin (Al Makki Health Informatics Journal, 2024)
Pneumonia is an acute infectious disease that affects the alveoli and is caused by specific microorganisms, characterized by symptoms of coughing and shortness of breath. In the case of 2019, WHO recorded the most deaths in the world caused by pneumonia, reaching a total of 62,782 cases. In Indonesia alone, in 2021, there were 2.56 million confirmed cases of pneumonia. The prevalence of pneumonia in West Java reached 2.6%. This study aims to provide an overview of nursing care for pneumonia patients admitted to the emergency room of Gunung Jati Hospital. The method used is a descriptive method with a case study design. The results of this study indicate that the intervention carried out for 1 x 7 hours with the cooperation of the emergency room nurse had a positive impact. The author has carried out actions by the nursing plan that has been made. The implementation of Evidence-Based Practice (EBP) Pursed Lift Breathing (PLB). Deep Breathing Exercise (DBE) affects the patient's breathing frequency. Before the implementation of the intervention, the patient's breathing frequency (Respiratory Rate / RR) was 28 x/min. After implementing the intervention, the patient's breathing frequency dropped to 26 x/min. It can be concluded that the pursed lift breathing intervention can significantly reduce shortness of breath in patients with pneumonia. The implication of this study is the importance of applying appropriate and measurable interventions in nursing care for pneumonia patients to improve the quality of care and minimize the risk of complications.